EFFECTS OF DIFFERENT PROCESSING METHODS ON THE RESISTANT STARCH CONTENT OF SOME LEGUMES - Michael , K. G.; Sogbesan, O. A.; Onyia, I. U. (FUDMA JOURNAL OF SCIENCES, 2021)
This work describes the effects of different processing methods on resistant starch (RS) contents of Canavalia ensiformis, Detarium microcarpum, Jatropha curcas and Glycine max. meals. The legume seeds were subjected to different processing methods (Raw, soaked, Boiled, Toasted and Fermented). Resistant Starch was determined by Megazyme Resistant Starch Assay procedure (A.O.A.C, 2002). In the results, the highest resistant starch contents were recorded in the toasted method for the three legume meals (Canavalia ensiformis 11.69 %, Detarium microcarpum 10.49 %, Jatropha curcas 13.06 %, while in Glycine max. 12.0 % was recorded in the boiled method). The lowest resistant starch contents were recorded in the raw processing method for the three legume meals (Canavalia ensiformis 8.47 %, Detarium microcarpum 7.25 %, Jatropha curcas 9.13 %, while in Glycine max. 7.51 % was recorded in the soaked method). The results of this research have proven the type 3 (RS3) resistant starch, which is retrograded starch made by cooking/cooling processes on starchy materials. Data were analyzed using one-way ANOVA and significant differences (p<0.05) were recorded among the different processing methods